Pengaruh alkali terhadap pengeluaran kulit biji, mutu giling danwarna tepung biji sorgum=Effect of Alkali Debulling on Pearled Grain, Milling Quality,and Flour Colour Sorghum Grain - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1990)
The effect of alkali dehulling on pearled grain, milling quality, and flour colour of sorghum grain was under study. Aqueous solutions of sodium hydroxide (NaOH) as dehulling agents hulled grain. Four soaking periods (5